A comparison of negative pressure wound therapy modalities, VAC versus non-commercial NPWT alternatives: A systematic review of RCTs/CCTs. Issue 4 (November 2022) - Madrigal, Paloma; Moshal, Tayla; Bernabe, Rendell; Yenikomshian, Haig; Gillenwater, Justin
Abstract: Background: Negative pressure wound therapy (NPWT) has been described as an effective treatment for wounds of various etiologies, however it is expensive. Various authors have investigated low-cost alternatives to commercial NPWT devices. A systematic review summarizing their findings is needed for clinicians operating in resource-limited locations and for those interested in potential cost savings. Methods: A systematic review was performed evaluating articles from Cochrane, PubMed and EMBASE. The studies included randomized controlled trials (RCTs) and controlled clinical trials (CCTs) that compared commercially available Vacuum-Assisted Closure (VAC) devices with non-commercial NPWT modalities in human subjects. Results: Seven hundred and ninety-six articles were retrieved, of which six met inclusion criteria. All six studies were RCTs and had in total 409 participants with wounds of various etiologies, including acute, chronic, and traumatic wounds. All studies compared VAC to a non-commercial NPWT device. Five studies were found to have low risk of bias, and one study had high risk of bias. There were three types of non-commercial NPWT devices used: wall suction applied to a sealed gauze dressing (GSUC), AquaVac, and Redon drains. The following outcomes were assessed: granulation tissue formation, effect on wound size area, skin graft take, pain/time associated with dressing changes and cost. In trials that compared GSUC vs VAC, there was no significant difference between the two groups for the following outcomes: granulation tissue formation, effect on wound size and skin graft take. GSUC dressings were significantly less painful and less time-consuming than VAC dressings. In the trial that compared AquaVac vs VAC, there was no significant difference between the two groups for the following outcomes: granulation tissue formation, effect on wound size, and the time or pain associated with dressing changes. In the trial that compared Redon drains vs VAC, there was significantly more granulation tissue formed in the VAC group. All non-commercial NPWT devices were found to be less costly than VAC. Conclusion: The data from the trials evaluated in this review indicate that GSUC and AquaVac are two non-commercial NPWT devices that are non-inferior to VAC for various outcomes while also being less costly. GSUC was less painful and less time-consuming than VAC. Of the non-commercial NPWT devices evaluated in this review, GSUC had the most evidence to support its future use. Prospective, multi-institutional RCTs with a large sample size are needed to confirm the findings presented here. Highlights: Wound healing. Low cost NPWT modalities. Socio-economic issues.